2016
DOI: 10.1007/s12288-016-0670-2
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study of Pegaspargase, Gemicitabine, Oxaliplatin and Dexamethasone (Peg-GemOD) as a First-Line Therapy for Advanced-Stage Extranodal NK/T Cell Lymphoma

Abstract: This study was conducted to retrospectively investigate the efficacy and safety of pegaspargase, gemicitabine, oxaliplatin and dexamethasone (PegGemOD) combination chemotherapy as a first-line therapy for advanced-stage extranodal NK/T cell lymphoma (ENKTL). Eighteen patients with newly diagnosed stage III/IV ENKTL were subjected to 3-6 cycles of PegGemOD chemotherapy. After 3 cycles of therapy, the overall response rate was 67 % (12/18) with a complete response rate of 28 % (5/18) and a partial response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Several studies have demonstrated that stage III/IV ENKTL patients with primary site of upper aerodigestive tract have a more favorable clinical outcome than those originating in non-upper aerodigestive tract. 18 Similar to these researches, our result showed that the response rate and 3-year survival rate was significantly higher in patients with UAT advanced stage ENKTL, indicating that this unique group of patients may be different in the pathogenesis and need to be explored as a single entity.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have demonstrated that stage III/IV ENKTL patients with primary site of upper aerodigestive tract have a more favorable clinical outcome than those originating in non-upper aerodigestive tract. 18 Similar to these researches, our result showed that the response rate and 3-year survival rate was significantly higher in patients with UAT advanced stage ENKTL, indicating that this unique group of patients may be different in the pathogenesis and need to be explored as a single entity.…”
Section: Discussionsupporting
confidence: 83%
“…Conclusively speaking, the present cohort achieved an mOS of 26.07 months and an estimated 5-year OS of 41.3%, much more gratifying than previously reported in retrospective real-world settings [11, 12, 15, 19, 36‒38]. First, CT with efficient regimen, standard dose, and duration could contribute to maximizing the survival benefit.…”
Section: Discussionsupporting
confidence: 66%
“…The median number of MNC cells was 10.2 × 10 8 /kg (3.37–21.11 × 10 8 /kg), and that of CD34 + cells was 4.3 × 10 6 /kg (1.33–12.06 × 10 6 /kg). The median time to neutrophil engraftment was 12 8–15 days, and that of platelet engraftment was 15 7–21 days.…”
Section: Resultsmentioning
confidence: 99%
“…8 Overtime, asparaginase-based chemotherapy regimens have been used mainly for patients with ENKTL, and the survival rate after 5 years was about 40%. [9][10][11] American Society for Blood and Marrow Transplantation (ASBMT) suggested that hematopoietic stem cell transplantation should be used as a first-line treatment. 12 Till date, optimal treatment strategies and prognosis for patients with advanced ENKTL have not been fully defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation